The princess diaries [videorecording (DVD)] - Hathaway, Anne, 1982-; Matarazzo, Heather, 1982-; Elizondo, Hector; Moore, Mandy, 1984-; Cabot, Meg (Disney DVD., 2001)
Your basic Cinderella makeover story with a fresh and affectionate twist. Mia is a frizzy-haired, glasses-wearing 15-year-old girl whose two highest ambitions are to become invisible and to get a few kisses from an attractive school heartthrob. She is stunned and horrified when her coolly continental grandmother shows up and informs her that she's the crown princess of the European principality Genovia. Soon enough, Mia has to undertake "princess lessons" (and a makeover) from her queenly grandmother, and eventually she blossoms into a confident, radiant girl.